Factor analysis of Pregnant Women's Concerns Scale of Contracting COVID-19 questionnaire - Bilgin, Zümrüt; Aktaş, Büşra (Universitas Airlangga, 2023)
Introduction: The global pandemic caused by the emergence of COVID-19 resulted in increased anxiety, notably among pregnant women. Uncertainties linked to the increased concerns due to virus and this led to realizion of emphasing the necessity for tools to evaluate the fear contracting it. This study aims to create a Scale for Pregnant Women's Concerns of being Contracted to COVID.Methods: A preliminary 5 point Likert-type scale comprising 29 items was distributed among 285 pregnant women. The statistical analysis conducted on the responses from 285 invidividuals that contracted COVID-19. The scale's validity and reliability were assessed through exploratory and confirmatory factor analysis, also the outcome of computation Cronbach's alpha coefficients taken into assesment. Results: According to the factors analysis the scale components consisting 12 items, and 2 factors explained 51.81% of the overall variation. The Cronbach's alpha internal consistency coefficient was determined to be 0.828. The Pregnant Women's Concerns Scale for Contracting COVID-19 is a valid scale for Turkish pregnant women. Conclusion: Psychosocial characteristics of pregnant women affect their concerns of contracting COVID-19. It is recommended to apply this scale to sample groups from different cultures. This scale is a valid and reliable instrument for evaluating pregnant women's apprehensions regarding COVID-19 infection. Implementing this scale within prenatal health services will aid in identifying and addressing COVID-19 related concerns among individuals at an early stage pregnancy. Keywords: COVID-19 concern; pregnancy; reliability; scale development; validity